A review on the biomass pretreatment and inhibitor removal methods as key-steps towards efficient macroalgae-based biohydrogen production. (November 2017) - Shobana, Sutha; Kumar, Gopalakrishnan; Bakonyi, Péter; Saratale, Ganesh D.; Al-Muhtaseb, Ala'a Hamed; Nemestóthy, Nándor; Bélafi-Bakó, Katalin; Xia, Ao; Chang, Jo-Shu
Highlights: This review focused on the generation of biohydrogen from macroalgae. Key issues affecting H2 production via dark fermentation are presented. Discussed various strategies for 5-HMF removal and detoxification. Abstract: (Red, green and brown) macroalgal biomass is a propitious candidate towards covenant alternative energy resources to be converted into biofuels i.e. hydrogen. The application of macroalgae for hydrogen fermentation (promising route in advancing the biohydrogen generation process) could be accomplished by the transformation of carbohydrates, which is a topic receiving broad attention in recent years. This article overviews the variety of marine algal biomass available in the coastal system, followed by the analyses of their pretreatment methods, inhibitor formation and possible detoxification, which are key-aspects to achieve subsequent H2 fermentation in a proper way.